Design of a blue LED stimulation unit with a highly uniform illumination pattern - Quesada, I.; Otazo, M. R.; Baly, L.; Gonzalez, Y. (Ancient TL, 2004)
The current study is concerned with the design and construction of a blue LED stimulation unit with a highly uniform illumination pattern. The pattern produced by a single LED is characterized experimentally. Using this information and making certain approximations, the illumination pattern produced by an array of LEDs was computer generated, and the mean intensity and relative standard deviation were calculated. In this way, several hypothetical configurations were evaluated; the most convenient configuration was constructed and experimentally characterized. The measured uniformity expressed as the relative (to the mean intensity) standard deviation in the sample zone was as good as 1.7%.